2013
DOI: 10.1007/978-94-007-5881-0_1
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome P450 2E1: Its Clinical Aspects and a Brief Perspective on the Current Research Scenario

Abstract: Research on Cytochrome P450 2E1 (CYP2E1), a key enzyme in alcohol metabolism has been very well documented in literature. Besides the involvement of CYP2E1 in alcohol metabolism as illustrated through the studies discussed in the chapter, recent studies have thrown light on several other aspects of CYP2E1 i.e. its extrahepatic expression, its involvement in several diseases and pathophysiological conditions; and CYP2E1 mediated carcinogenesis and modulation of drug efficacy. Studies involving these interesting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 272 publications
(717 reference statements)
0
6
0
1
Order By: Relevance
“…Although drug interaction studies are not specified in the FDA guidance for CYP2A6 and CYP2E1, these enzymes may also cause drug-botanical interactions. CYP2A6 is involved in the metabolism of some tobacco compounds including nicotine, cotinine and N 1 -nitrosonornicotine (Pelkonen et al, 2000), and CYP2E1 has been reported to metabolize ethanol, caffeine, acetaminophen, and chlorzoxazone (Hrycay and Bandiera, 2008; Dey 2013). In this study, we used a cocktail assay approach (Li et al ., 2015) with ultrahigh-pressure liquid chromatography-tandem mass spectrometry (UHPLC-MS/MS) to measure possible inhibition of all seven CYP isoforms recommended by the FDA as well as CYP2A6 and CYP2E1 by extracts of G. glabra, G. uralensis and G. inflata and 14 compounds (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Although drug interaction studies are not specified in the FDA guidance for CYP2A6 and CYP2E1, these enzymes may also cause drug-botanical interactions. CYP2A6 is involved in the metabolism of some tobacco compounds including nicotine, cotinine and N 1 -nitrosonornicotine (Pelkonen et al, 2000), and CYP2E1 has been reported to metabolize ethanol, caffeine, acetaminophen, and chlorzoxazone (Hrycay and Bandiera, 2008; Dey 2013). In this study, we used a cocktail assay approach (Li et al ., 2015) with ultrahigh-pressure liquid chromatography-tandem mass spectrometry (UHPLC-MS/MS) to measure possible inhibition of all seven CYP isoforms recommended by the FDA as well as CYP2A6 and CYP2E1 by extracts of G. glabra, G. uralensis and G. inflata and 14 compounds (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Under normal conditions, CYP2E1 accounts for 10% of ethanol oxidation, but it is inducible by chronic ethanol ingestion [ 8 ]. Enhanced CYP2E1 activity not only causes increased ROS formation but also results in an increased activation of various environmental pro-carcinogens that require CYP2E1 to be activated [ 3 , 9 ]. MEOS plays a major role in the oxidation of ethanol, as well as the formation of ROS, appearing to be mechanism for hepatotoxic-induced ethanol [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…CYP2E1 plays an important role in the metabolic clearance of pollutants (aniline and styrene) and beverages (ethanol), and its activity is also involved in the hepatotoxic effects of many drugs, such as acetaminophen, an analgesic-antipyretic agent widely used, and cisplatin, an anticancer agent. Interactions between acetaminophen or cisplatin and CYP2E1 generate reactive metabolites and reactive oxygen species [25][26][27]. So, an increase CYP2E1 activity may also potentiate the risk of hepatotoxic effects caused by the accumulation of toxic compounds in the body that lead to oxidative stress, liver injury, and other detrimental effects.…”
Section: Resultsmentioning
confidence: 99%